Impact of Normal and Overweight Pregnant Women upon Neonatal Outcomes in Al-Nasiriya Hospitals :Comparative Study - Sara Ahmed Rashed; Rabea Mohsen Ali (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Maternal obesity is a major risk for both the mother and the fetus, and it is considered anobstetrical risk factor that leads to a high incidence of complications throughout the prenatal period, aswell as an increased risk of many adverse pregnancy outcomes.Objectives: To assess the impact of normal and overweight pregnant women upon Neonatal outcomesat Al-Nasiriya city.Methodology: A descriptive analytic study was conducted from January11th, 2021 to March 18th, 2021at Al-Nasiriya City Hospitals for Maternity and Children on(100) pregnant women who attending laborroom , (50) were overweight and (50) normal weight pregnant women with gestational age for 08-40weeks were included . A non–probability (Purposive sample) was used to select the participants ofstudy sample.Results: The result of study revealed that (34.1%) (36.4%) of study sample aged (26-30) years innormal, and overweight pregnant respectively. The study results clarifies the previous and current bodymass index among normal weight pregnant women (100% & 95% ) respectively, while in overweight(63.6%) overweight previously and (65.9%) obesity class ( I) at current. the impact of weight uponneonate outcomes; the findings indicates that weight has significant impact up on outcomes related toneonate, at p-value= 0.006, while there is no impact has been reported among group of normal weightpregnant women.Conclusion: The study concluded that overweight impact upon outcomes related to neonate condition,while there is no impact has been reported among group of normal weight pregnant women.Recommendations: Increased physical activity and knowledge of healthy eating habits among pregnant women as part of primary health care centre initiatives to reduce obesity in women.